1997
DOI: 10.1007/bf02062016
|View full text |Cite
|
Sign up to set email alerts
|

Undetectable expression of hMLH1 protein in sporadic colorectal cancer with replication error phenotype

Abstract: hMLH1 protein was undetectable in the two tumor tissues of the six replication error-positive samples of sporadic colorectal cancer. The detection procedure used here may have potential use for determining a dysfunctional mismatch repair gene product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Specific monoclonal or polyclonal antibodies for p53 , gastric and intestinal mucin (gastric mucin, mouse monoclonal antibody NCL‐HGM‐45M1; intestinal mucin; mouse monoclonal antibody NCL‐MUC‐2; Novocastra, Newcastle, UK), hMLH1 (clone G168–728; Pharmingen, San Diego, CA, USA) and hMSH2 25 were used with the avidin–biotin–peroxidase technique 12,26 . We defined grades as follows: +, more than 50% of the cancer cells showing clear positive staining in comparison with the background and the negative control; −, more than 90% of the cancer cells showing no staining (that is, specimens could not be differentiated from the background and negative control); +/−, borderline specimens.…”
Section: Methodsmentioning
confidence: 99%
“…Specific monoclonal or polyclonal antibodies for p53 , gastric and intestinal mucin (gastric mucin, mouse monoclonal antibody NCL‐HGM‐45M1; intestinal mucin; mouse monoclonal antibody NCL‐MUC‐2; Novocastra, Newcastle, UK), hMLH1 (clone G168–728; Pharmingen, San Diego, CA, USA) and hMSH2 25 were used with the avidin–biotin–peroxidase technique 12,26 . We defined grades as follows: +, more than 50% of the cancer cells showing clear positive staining in comparison with the background and the negative control; −, more than 90% of the cancer cells showing no staining (that is, specimens could not be differentiated from the background and negative control); +/−, borderline specimens.…”
Section: Methodsmentioning
confidence: 99%
“…Mismatch repair defects are the basis for the microsatellite instability found in hereditary nonpolyposis colorectal cancer (HNPCC) and in a significant fraction of sporadic colorectal cancers and certain other sporadic tumors [Ionov et al, 1993;Fishel et al, 1993;Parsons et al, 1993;Peltomaki et al, 1993;Thibodeau et al, 1993;Aaltonen et al, 1994;Umar et al, 1994;Li and Modrich, 1995]. The majority of these defects are in the hMLH1 or hMSH2 genes [Bronner et al, 1994;Hemminki et al, 1994;Koike et al, 1997;Benanchenhou et al, 1998;Cunningham et al, 1998;Guerrette et al, 1998;Herman et al, 1998]. …”
Section: Introductionmentioning
confidence: 98%
“…The dashed lines show the relative amount of probe À107C or À107G required to bind the same amount of nuclear protein À107G allele is insufficient to evaluate the difference of clinicopathological properties between À107C and À107G patients. For the MSI status, tumors of two patients had the microsatellite stable (MSS) phenotype and one had an MSI-H phenotype, which was due to hMSH2 deficiency (Koike et al 1997. Thus, although the À107G allele was found only in the cancer population, the correlation between hMLH1 repression exerted by the À107G substitution and the carcinogenesis of these patients remains to be elucidated.…”
Section: Clinicopathological Properties Of Tumors With à107g Allelementioning
confidence: 98%
“…We have previously investigated expression of hMSH2 and hMLH1 proteins in tumor tissues of colorectal cancer patients (Koike et al 1997Zhong et al 2001). We found that approximately 6-7% of cases had reduced or absent hMLH1 protein and mRNA expression.…”
Section: Introductionmentioning
confidence: 98%